Legal Protection for Vehicle Owners in Lawsuits for Unlawful Acts of Confiscation of State Land: Review of Decision 27/Pdt.G/2019/Pn.Tbk - Handika Ramadhan; Muhammad Insa Ansari; Muhammad Adli (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the legal protection of the owner of the means of transportation in cases of unlawful acts (PMH) related to state deprivation, based on the Study of Decision Number 27/Pdt.G/2019/Pn.Tbk. The main focus of this study is to analyze the legal position of the owner of the transportation facilities who are not directly involved in the crime, but suffer losses due to acts of confiscation by the state. The research method used is empirical normative with a case study approach. The results of the study show that the court in the decision did not provide adequate protection for the civil rights of the owner of the means of transport, even though there was no evidence of direct involvement in the crime. This decision indicates the weak legal protection for third parties in good faith and the importance of strengthening the principle of due process of law in the process of confiscation by the state so as not to violate legitimate civil rights. This study recommends the need for a clearer regulation of the mechanism of objection and restoration of rights for parties aggrieved by acts of state deprivation.